Engineering properties of Batu Pahat soft clay stabilized with lime, cement and bentonite for subgrade in road construction - Che Mamat, Rufaizal (2013)
Constructions on soft clay are often affected by stability and settlement problems. Ground improvement methods have been used in many parts of the world to minimize these problems. The aim of this research is to evaluate the engineering properties of Batu Pahat Soft Clay (BPSC) mixed with three types of admixtures. This research presents the stabilization of BPSC using admixtures lime, cement and natural sodium bentonite at varying binder contents (5%, 10%, 15%, 20% and 25%). The basic soil properties such as compaction, unconfined compression strength, California bearing capacity and permeability testing methods were used to gauge the behavior and performance of the stabilized soils. From the tests conducted, the researcher has found that the addition of lime, cement and natural sodium bentonite decreased the maximum dry density and increased the optimum moisture content. The tests conducted gave some indication that the unconfined compressive strength increased with the percentage of stabilizer and curing periods for cement treated sample compared to lime and bentonite treated sample. It also showed that an increase in the binder content and curing periods results in a reduction of the permeability of the stabilized soils. The results of California Bearing Ratio (CBR) indicated that the increase of curing periods and percentage of stabilizers led to an increase in the CBR values for cement treated sample compared to lime and bentonite treated sample.